دراسة تحليلية لعائدات أملاك البلدية المنتجة للمداخيل-دراسة حالة بلدية مغنية (2012-2019) (El-Wahat Journal for Research and Studies, 2023)
ملخص:تعد أملاك البلدية المنتجة للمداخيل من أهم المصادر التي تمول ميزانية البلدية حيث تعتبر مورد دائم يمكن تطوريه بصورة مستمرة إذا ما تم إستغلالها على أحسن وجه، لكن الواقع هو أن معظم البلديات في الجزائر تعرف نقص في هذه الموارد نتيجة الإهمال الذي طال العديد منها وسوء تسييرها الذي ينعكس بصورة مباشرة على الإيرادات المالية للبلدية. وعليه جاء هذا المقال للوقوف على واقع عائدات أملاك البلدية المنتجة للمداخيل وكعينة للدراسة تم القيام بدراسة تحليلية لتطور عائدات أملاك بلدية مغنية للفترة الممتدة من 2012 إلى 2019 ومدى مساهمتها في أجمالي الإيرادات، وتم التوصل إلى أن أملاك البلدية المنتجة للمداخيل لا تساهم بالقدر الكافي في تمويل إيرادات البلدية، وتدهور بعض الممتلكات العقارية التابعة للبلدية نتيجة الإهمال والتهميش الذي تتلقاه وضعف تسيير هذه الموارد. كلمات دالة: أملاك البلدية، إيرادات مالية، ميزانية البلدية         Abstract: Municipal Property That Produces Revenues Is One Of The Most Important Sources That Finance The Municipality's Budget, As It Is Considered A Permanent Resource That Can Be Continuously Developed If It Is Used In The Best Way. It Is Directly Reflected In The Municipality's Fiscal Revenues. Accordingly, This Article Came To Find Out The Reality Of The Revenues Of Municipality Properties That Produce Revenues And As A Sample For The Study. An Analytical Study Was Conducted On The Development Of The Revenues Of Maghnia Municipality Properties For The Period From 2012 To 2019 And The Extent Of Their Contribution To The Total Revenues. And It Has Been Concluded That The Municipal Income-Producing Properties Of The Incomes Do Not Contribute Enough To The Financing Of The Municipal Revenues. And The Deterioration Of Some Real Estate Belonging To The Municipality As A Result Of Neglect, Marginalization And Poor Management Of These Resources.Key Words: Municipal Property, Fiscal Revenues, Municipal Budget